(untitled) (CIPEEX, 2022)
INTRODUCTION: INTENSIVE CARE UNITS (ICUS) ARE RESPONSIBLE FOR RECEIVING PATIENTS IN A CRITICAL STATE OF HEALTH. THUS, THE NEONATAL ICU IS UNDERSTOOD AS THE AREA WITHIN A HEALTH UNIT RESPONSIBLE FOR HOSTING AND TREATING PREMATURE BABIES OR WITH ANY CRITICAL HEALTH PROBLEM. IN THE CASE OF BABIES FROM 0 TO 28 DAYS PREMATURE TO MATURE THE LUNGS, GAIN WEIGHT AND TREAT CONGENITAL AND GENETIC DISEASES. OBJECTIVES: GENERAL: TO IDENTIFY IN THE SCIENTIFIC LITERATURE HOW THE HOSPITALIZATION IN THE NEONATAL ICU IS DESCRIBED; SPECIFIC: TO KNOW HOW THE FAMILY DESCRIBES THE HOSPITALIZATION IN THE NEONATAL INTENSIVE CARE UNIT; TO KNOW HOW THE PROFESSIONALS DESCRIBE HOSPITALIZATION IN NEONATAL ICU. METHODOLOGY: THIS IS A LITERATURE REVIEW RESEARCH. WE USED MEANS IN AN ONLINE LIBRARY OF SCIELO (SCIENTIFIC ELECTRONIC LIBRARY ONLINE), VHL (VIRTUAL HEALTH LIBRARY) AND LILACS (LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCE) DATABASES AND BDENF (NURSING DATA BASE) WITH DESCRIPTORS IN HEALTH: WITH DESCRIPTORS IN HEALTH: NURSING, NEONATAL NURSING, HOSPITALIZATION, NEONATAL ICU. RESULTS: TWO CATEGORIES EMERGED THAT BECAME MORE EVIDENT: FIRST, THE FAMILY VIEW REGARDING HOSPITALIZATION IN A NEONATAL INTENSIVE CARE UNIT; SECOND, VIEW OF HEALTH PROFESSIONALS REGARDING HOSPITALIZATION IN NEONATAL ICU. CONCLUSION: THE HOSPITALIZATION IN THE NICU IS SEEN AS A PLACE FULL OF FEELINGS OF LOSS, SADNESS, ANGUISH AND DESPAIR, AT THE SAME TIME THERE IS THE FEELING OF HOPE FOR A BETTER FUTURE AND AT HOSPITAL DISCHARGE AND FEEL VERY HAPPY WHEN THEY ARE ALLOWED AND GUIDED TO PARTICIPATE IN THE CARE OF THE CHILD DURING THE VISIT, TO PARTICIPATE IN DIAPER CHANGES TO PROMOTE AFFECTIVE BONDS.FOR HEALTH PROFESSIONALS IS A PLACE OF MUCH EMOTIONAL, PSYCHOLOGICAL AND PHYSICAL WEAR AND TEAR, THEY ARE CONCERNED ABOUT WELCOMING THE FAMILY IN THE BEST WAY TO PROMOTE MORE PEACE OF MIND , TRUST AND FAMILY BOND, ARE CONCERNED WITH THE DEVELOPMENT OF THE NEWBORN, WITH PAIN, FEVER AND PREVENTION OF INFECTIONS THAT CAN LEAD TO NEONATAL DEATH. THE PROFESSIONALS WHO WORK IN THIS AREA NEED TECHNICAL UPDATING, SCIENTIFIC AND CONTINUING EDUCATION AND PERMANENT TO BETTER CARE FOR THEM. THIS WORK WILL SERVE AS THE BASIS FOR NEW SCIENTIFIC RESEARCH.